Stepwise regression modeling for compressive strength assessment of mortar containing metakaolin. (2nd October 2018) - Hosseinpour, Mahmoud; Sharifi, Hojjat; Sharifi, Yasser
Abstract: A stepwise regression (SR) model is developed as a reliable modeling method for simulating and predicting the compressive strength of mortars containing metakaolin at the age of 3, 7, 28, 60, and 90 days. The required data in training and testing state obtained from a reliable data base. A new formulation based on the model have been proposed to predict the compressive strength of mortars containing metakaolin. Besides, to model verification a nonlinear least squares regression (NLSR) has been also developed. Then, a comparison has been made between the proposed SR formulae and NLSR to have an idea about the predictive power of the SR method.